1997
DOI: 10.1002/(sici)1097-0169(1997)36:1<30::aid-cm3>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of filamentous actin organization in the sea urchin egg cortex during early cleavage divisions: Implications for the mechanism of cytokinesis

Abstract: We have used confocal laser scanning microscopy in conjunction with BODIPY‐phallacidin staining of filamentous actin to investigate changes in the quantity and organization of cortical actin during the first two cell cycles following fertilization in eggs of the sea urchin Strongylocentrotus purpuratus. Quantification of fluorescent phallacidin staining reveals that the amount of filamentous actin (F‐actin) in the cortex undergoes cyclical increases and decreases during early cleavage divisions, peaking near t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 52 publications
(71 reference statements)
2
17
0
Order By: Relevance
“…after treatment with jasplakinolide (this study) or in sea urchin eggs following fertilization (Wong et al, 1997). Another example is during microvillar formation in intestinal epithelial cells which begins in the crypts of Lieberkuln and continues on the villus before its cells are sloughed away from the villus tip 2-3 days later (Fath et al, 1990;Mamajiwalla et al, 1992).…”
Section: Microvillar Dynamicsmentioning
confidence: 90%
“…after treatment with jasplakinolide (this study) or in sea urchin eggs following fertilization (Wong et al, 1997). Another example is during microvillar formation in intestinal epithelial cells which begins in the crypts of Lieberkuln and continues on the villus before its cells are sloughed away from the villus tip 2-3 days later (Fath et al, 1990;Mamajiwalla et al, 1992).…”
Section: Microvillar Dynamicsmentioning
confidence: 90%
“…It has been widely suggested that microvilli, which increase the surface area of sea urchin eggs 4-fold (34), might easily provide the required increase in surface area during cytokinesis. However, measurements of microvillar length through the cell cycle indicate that microvilli are not a likely source of membrane (34,35). The appearance of new hyalin at the cell surface after mitotic exit (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were then fixed and permeablized using a protocol optimized for visualizing the actin cytoskeleton (Wong et al, 1997). Cells were then washed, blocked with 3% bovine serum albumin in phosphate-buffered saline/2 mM NaF, and processed for tubulin (DM1A; Sigma-Aldrich), activated myosin II [rabbit or mouse anti-phospho(Ser19)-myosin regulatory light chain; Cell Signaling Technology, Beverly, MA], or egg myosin II localization.…”
Section: Detection Of Ser19 Phosphorylation In Vivomentioning
confidence: 99%